ERP's function as a moderating factor in accounting quality and audit attributes - Merlyana Dwinda Yanthi; Isnalita Isnalita (Journal of Innovation in Business and Economics, 2025)
The objective of this research is to investigate how specific audit characteristics impact the quality of financial statements in manufacturing firms and whether enterprise resource planning (ERP) can enhance the relationship between audit attributes and accounting quality. The study analyzes a sample of 940 manufacturing companies listed between 2018 and 2022. Data analysis was conducted using basic linear regression and Moderated Regression Analysis (MRA). The findings indicate that ERP does not enhance the effect of audit tenure on accounting conservatism and earnings management. However, ERP appears to weaken the influence of auditor specialization on these measures of accounting quality. This study contributes to the existing literature by extending the analysis of audit tenure and accounting quality through the inclusion of ERP as a moderating variable.